Resistance and resilience: the importance of the Family Farming Market in Armação dos Búzios, Rio de Janeiro, Brazil - da Cunha Guterman, Gustavo; Moreira Santos, Erika Vanessa (Geografares, 2025)
Family farming is central to valuing food culture, with its multiplicity of knowledge practices and foods. Open-air markets are a short supply–chain strategy that gives visibility to diversified family production. This article examines the Family Farming Market in Búzios as a territory of resistance for the production of smallholders, quilombola communities, and fishers. The methodology combined documentary and regulatory review, fieldwork, and semi-structured interviews with vendors and the market organizer. The material was systematized and analyzed in light of the importance of food culture and the valorization of territories of “re-existence,” with particular emphasis on the Family Farming Market of Armação dos Búzios, Rio de Janeiro, Brazil. The findings show that the market mobilizes multiple spheres of society through the power of food—from production to sale and consumption—constituting a space of political resistance and the affirmation of food culture.
Keywords: food culture; short supply chains; territory